Probing Self-Interacting Dark Matter Models with Neutrino Telescopes - Sotelo, Denis Stefan Robertson (2017)
In this thesis we studied dark matter models with strong self-interactions, typically known as self-interacting dark matter (SIDM). This kind of models constitute a promising solution to the tension between small scale structure observations and predictions assuming the standard case of collisionless cold dark matter (CDM) while keeping the success of the standard cosmological model, LambdaCDM, at large scales. The presence of strong self-interactions can increase the dark matter capture and annihilation in astrophysical objects like our sun, enhancing the potential of indirect detection signals. We used the high energy neutrinos produced by such annihilations to probe SIDM models. We established strong constraints on SIDM with velocity independent cross section by comparing the expected neutrino signal with the results of the IceCube-79 dark matter search. Also, we determined the sensitivity for the IceCube-DeepCore and PINGU detectors for SIDM with a velocity dependent self-interacting cross section (vdSIDM). Most of its relevant parameter space can be tested with the three years of data already collected by IceCube-DeepCore, complementing results from direct detection experiments and other indirect detection studies.